Peran selenium sebagai antioksidan pada dyspepsia fungsional anak - Bia Safitri; Atan BA; Supriatmo dr (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Functional dyspepsia is common disorder of the upper gastrointestinal tract, occurring in 26% to 34% of the general population and very common in children with 80% with chronic abdominal pain. In the last one and a half decades, the concept of free radical mediated oxidative stress has gain tremendous scientific momentum right from studying its role in the pathophysiology of disease to its therapeutic implications. Almost all gastrointestinal diseases have been evaluated for underlying Oxidative stress as a causative factor and intervention with antioxidants attempted it. Selenium is one of many antioxidants. Selenium is an essential component of the enzyme glutathione peroxidase, which functions as part of an antioxidant system to protect cells from the potential damaging effect of reactive oxygen. The result in these studies have been limited, but the antioxidant function of selenium plays protective roles in human disease, including prostate, stomach, lung, colon cancer, immunodeficiency and heart disease, its known as enzymes effect of selenium.Keywords : functinal dyspepsia; oxidative stress; selenium